Dekryminalizacja przestępstwa (nieświadomie) nieumyślnego? [Decriminalisation of the crime of (inadvertent) negligence?] (Studia Prawnicze / The Legal Studies, 2014)
Obserwacja rozwoju prawa karnego prowadzi do konkluzji, że stopniowo, ale konsekwentnie rozszerza się zakres penalizacji poprzez wprowadzanie nowych typów przestępstw nieumyślnych. Jako uzasadnienie takiej tendencji wielokrotnie wskazywano na postępujący rozwój techniki. Zarazem jednak w nauce prawa karnego reprezentowany jest pogląd, że karalność przestępstw nieumyślnych jest rzeczą niewłaściwą, i winna zostać, jeśli już nie całkowicie zniesiona, to przynajmniej w pewnym zakresie ograniczona. Właściwym środkiem reakcji na takie czyny ma być odpowiedzialność cywilna w postaci zadośćuczynienia za wyrządzaną szkodę (krzywdę). Wydaje się, że jeżeli nie ze względu na niebagatelne autorytety stojące za nim, to na pewno ze względu na wartość argumentacyjną, pogląd taki, prezentowany szczególnie wyraźnie na gruncie doktryny niemieckiej i anglosaskiej, wymaga pewnego rozważenia i zajęcia stanowiska. The author considers the reasonableness of the recently proposed – especially in the German and Ango–American science of Criminal Law – postulates of decriminalization of the unintentional crimes. The analysis of those propositions reveals that they are based on questioning the possibility of proving guilt of the perpetrator of inadvertently negligent crime. Such doubts have generally not been shared by the Polish doctrine of criminal law, although authors considering this question seem have been aware of the special character of the criminalization of those crimes, where there is no culpability of the will.At the same time, the analysis of the formulated on the grounds of theory of criminalization premises of the creating penal prohibitions reveals that the unintentional crimes, especially of inadvertent negligence, fulfill those premises. It does not change the fact that this type of responsibility should be applied exceptionally, more rarely than it is currently the case in the Polish Criminal Law. The achievement of this purpose could be possible by replacing in case of some crimes the unintentionality clause with recklessness clause. The chance to reflect upon this question could be the current discussion upon the changes in the Polish Criminal Code.